Convention on the Prevention and Punishment of the Crime of Genocide 1948. (A Study on its History, Content, and Importance) - Issa, Hussein Abd Ali; Othman, Lajan Mohammed Amin (Journal of Legal and Political Studies, 2020)
The research was devoted to studying the efforts of the United Nations in adopting the Convention on the Prevention and Punishment of the Genocide Crime of 1948 by analyzing the international documents issued by the committee, which were originally adopted in its drafting. It also clarifies the content of this Convention in regard to the concept of genocide, its forms and legal liability, the competent criminal tribunals, and the obligations of the States parties to it. Moreover, their importance in international and national law is explained. In addition, these themes are examined by dividing the research into three dimensions; the first will clarify the efforts of the United Nations in the drafting of the Convention, the second request will be devoted to its content, and the third one will review its importance.
Keywords: United Nations; Convention on the Prevention and Punishment of the Genocide Crime of 1948; concept of genocide; obligations of the States; dimensions